(untitled) - Sprague, Michael; Michael Sprague (Boston)
Cover all of the fundamentals of Visual Basic.net! This new book from established author, Michael Sprague, is a comprehensive instructional tool designed for an introductory course. Completely revised and updated, the second edition includes improved coverage of new topics and complete coverage of database programming, classes, collections. The book provides 75+ hours of instruction
Keywords: Microsoft Visual BASIC; BASIC (Computer program language); Microsoft .NET